PEMANFAATAN MEDIA KOMIK DIGITAL SEBAGAI MOTIVASI BELAJAR SISWA KELAS III MATERI KEBUDAYAAN - Alvin Jihan Safitri; Tasi’awati Salsa Kaliwanovia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the use of digital comics as an the learning motivation of third-grade students on cultural topics. This study was caused by the lack of student learning motivation influenced by the limitations of learning media and the still dominant use of lecture methods in learning activities. Digital comics were chosen because they can present cultural material through illustrated stories that are interesting, contextual, and easy to understand for elementary school students. This study uses a qualitative approach using descriptive methods. Data collection was carried out through observation, interviews, and documentation. The study findings indicate that the use of digital comics can increase students' interest, enthusiasm, and active participation in learning cultural topics. Students appeared more focused, motivated to read, and more easily mastered the concepts presented. Therefore, digital comics can be used as a good learning medium to increase the learning motivation of third-grade students, especially in cultural concepts